Isoflurane Is More Deleterious to Developing Brain Than Desflurane: The Role of the Akt/GSK3β Signaling Pathway. (1st February 2016) - Tao, Guorong; Xue, Qingsheng; Luo, Yan; Li, Guohui; Xia, Yimeng; Yu, Buwei
Abstract : Demand is increasing for safer inhalational anesthetics for use in pediatric anesthesia. In this regard, researchers have debated whether isoflurane is more toxic to the developing brain than desflurane. In the present study, we compared the effects of postnatal exposure to isoflurane with those of desflurane on long-term cognitive performance and investigated the role of the Akt/GSK3 β signaling pathway. Postnatal day 6 (P6) mice were exposed to either isoflurane or desflurane, after which the phosphorylation levels of Akt/GSK3 β and learning and memory were assessed at P8 or P31. The phosphorylation levels of Akt/GSK3 β and learning and memory were examined after intervention with lithium. We found that isoflurane, but not desflurane, impaired spatial learning and memory at P31. Accompanied by behavioral change, only isoflurane decreased p-Akt (ser473) and p-GSK3 β (ser9) expressions, which led to GSK3 β overactivation. Lithium prevented GSK3 β overactivation and alleviated isoflurane-induced cognitive deficits. These results suggest that isoflurane is more likely to induce developmental neurotoxicity than desflurane in context of multiple exposures and that the Akt/GSK3 β signaling pathway partly participates in this process. GSK3 β inhibition might be an effective way to protect against developmental neurotoxicity.